Privacy Implications Of Commercial Office Building Security Technology In The Post-9/11 Era - Adler, Trevor T. (Science and Technology Law Review, 2007)
This Note examines a full range of security issues involving privately-owned but publicly accessible office buildings in the post-9/11 era, from a landlord’s basic security duties to privacy infringement. The analysis focuses on the recent proliferation of computer-enabled access control and surveillance technologies, which have emerged in the last ten years as a viable alternative to increased security personnel staffing. The Note makes several conclusions and recommendations. First, to overcome the possibility of negligent security lawsuits, property owners must reevaluate the security provided in their buildings on an ongoing basis. Second, access control and surveillance technologies offer cost-effective means of satisfying security minima for a majority of commercial properties. Third, to balance the benefits of these technologies with the potential for privacy infringement, property owners should consider contractual and/or unilateral notice of security monitoring and recording practices. Finally, the burgeoning partnership between private security and law enforcement creates the possibility of Fourth Amendment privacy infringements.